Membangun Kesadaran Inklusif- Multikultural untuk Deradikalisasi Pendidikan Islam - Muqoyyidin, Andik Wahyun (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2013)
There are still many acts of terrorism that are as concrete evidences of how the use of the security approach alone isn’t effective enough to eradicate terrorism and Islamic radicalism to its roots in Indonesian. Therefore, various approaches of handling terrorism and Islamic radicalism must also be constantly pursued. That is the de-radicalization program through the nuances of Islamic education multicultural inclusiveness. In this case, they should pay attention to curriculum factors, educators, and educators use learning strategies.